Basic mechanisms for hillock formation during etching - Mirabella, D. A. (2008)
The formation of etch hillocks was explored in the framework of a site-dependent detachment probabilities model. Monte Carlo simulations were carried out for a one-dimensional substrate within a restricted solid-on-solid model in which only first neighbour interactions are considered. We specifically focus on describing the dynamics that lead to hillock-and-valley patterns. The mechanisms responsible for the steady state morphologies were related to apex creation and annihilation, together with valley and hillock etching, but pattern formation reflects two feedback loops that interrelate these mechanisms.